Hardware-based efficient Mickey-128 stream cipher with unrolling factors for throughput enhancement - Ananth, Raghavendra; Rao Malode V., Panduranga; Swamy Ramaiah, Narayana (Bulletin of Electrical Engineering and Informatics, 2025)
The emerging trend known as "ubiquitous computation" aims to incorporate intelligent gadgets into commonplace items. The lightweight cryptographic techniques are being researched and developed to minimize the gadgets' resources and a perpetual desire to reduce production expenses. A key element of symmetric cryptography, the stream cipher has unique benefits in terms of scalability as well as performance. The Mickey-128 stream cipher is designed and implemented in this manuscript. Additionally, unrolling features are incorporated with Mickey-128 cipher to enhance the throughput. The Mickey-128 contains a 128-bit key, an initialization vector (IV), and two clocking registers (R and S) with mapping units. The finite state machine (FSM) controller initializes and controls the key, IV and RS- registers data. The proposed Mickey-128 cipher runs on an Artix-7 field programmable gate array (FPGA) at 639.1 MHz and uses less than 1% of the chip's area (Slices). For unrolling factors 8 and 16, the Mickey-128 cipher achieves a throughput of 5.12 Gbps and 10.23 Gbps, accordingly. Finally, a comparison is made between the proposed Mickey-128 cipher and the existing ciphers' better hardware efficiency and throughput.